PSYCHOGRAPHIC SHEETS AND PERSONALITY CARDS OF PUPILS IN SCHOOLS OF WESTERN UKRAINE IN 1920s-1930s. - Mikhno, Oleksandr (Educological discourse, 2019)
By analyzing the works of Western Ukrainian scientists, it has been proved in this article that they worked in the context of scientific research that was characteristic of the European pedagogical thought of the 1920s and 1930s. The methods suggested by the scientists for studying a student and the main methodical ideas, namely, the use of psychographic schemes (Yakim Yarema, Mikhail Ostapovich, Dmitro Koziy), personality cards (Ivan Kukhta), observational cards and “free character references” of the personality (Volodymyr Bezushko), which served as a benchmark for teachers in their practical work to study the student and compile his character reference. The contents and structure of the psychographic schemes, which contained from 12 to 15 sections («Attention», «Memory», «Imagination», «Thought», «Method of Labor», «Tiredness», «Pain and Freedom», «Behavior in the Community», etc.) with detailed explanations of each of them. The structure of the personality card, which consisted of 6 items (appearance and physical development of the student, home conditions, attitude towards people, interest and aspiration, traits of character, temperament, mood, properties of mind) have been presented. The structure of pedology as realized by M. Baznyk, which, in his opinion, consists of several interrelated directions: psychopedology, physiopedology, pathological, laboratory pedology, testology, theoretical pedology, pedotechnics, moral pedology has been systematized. The article contains short biographical information about scientists-teachers whose articles are being analyzed.